Distribution and Pattern of an Insurance Health Claim System: A Time Series Approach - Mashasha, Maxwell; Mutize, Praise; Mazunga, Felix (College of Natural and Applied Sciences, University of Dar es Salaam, 2022)
There is a continuous increase in health costs, thereby increasing pressure on individuals and consequently making the amounts claimed by the insured to be on the increase. In this study, data was collected from a large local insurance company in Zimbabwe for the period from January 2012 to December 2016. The aim of this study was to analyse the distribution and future pattern of insurance health claim system using time series approach. Akaike information criterion and Schwarz Bayesian criterion were used to select the adequate model through maximum likelihood estimation methods. ARIMA (0, 0, 0) (1, 0, 1) [12] is the model that was chosen to forecast claim amounts. The use of ARIMA models proves to be an excellent instrument for predicting and capturing the cost trend of health claims which can help in decision making to insurance companies